Relationship between Panic Buying and Per Capita Income during COVID-19 - Yoshizaki, Hugo T. Y.; Brito Junior, Irineu de [UNESP]; Hino, Celso Mitsuo; Aguiar, Larrisa Limongi; Pinheiro, Maria Clara Rodrigues (Mdpi, 2020)
Panic buying and hoarding express common human behavior in times of crisis. Early in COVID-19, as the pandemic crisis intensified, toilet paper was one of the emblematic cases of panic buying. Using a Geographic Information System (GIS) to cross official per capita income data and real toilet paper transactions obtained from groceries spread around the city of Sao Paulo (Brazil), this study compares sales levels during the period in which panic purchases took place to the sales levels off that period. As expected, that data disclose noticeable panic buying. Regression analysis reveals that there is a significant positive correlation between average income per capita and panic buying. The results also indicate that panic buying happens in every income class, including low-income ones and contribute to enhancing the understanding of demand behavior during periods of crisis.
Keywords: panic buying; hoarding; per capita income; vulnerability; COVID-19; Sã o Paulo; grocery